2002
DOI: 10.1254/jjp.90.36
|View full text |Cite
|
Sign up to set email alerts
|

Contractile Responses and Myosin Phosphorylation in Reconstituted Fibers of Smooth Muscle Cells From the Rat Cerebral Artery

Abstract: ABSTRACT-String-shaped reconstituted smooth muscle fibers were prepared in rectangular wells by thermal gelation of a mixed solution of collagen and cultured smooth muscle cells derived from the rat cerebral artery. The fibers contracted in response to KCl, 5-hydroxytryptamine (5-HT), noradrenaline, endothelin-1, endothelin-2, angiotensin II, prostaglandin F 2= and prostaglandin E 2 . 5-HT-induced contraction was partially inhibited by the L-type voltage-dependent Ca 2+ channel inhibitor nifedipine, putative n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…However, responses to 5-HT were markedly enhanced in the AT 1A ϩ/ϩ mice (but not the AT 1A Ϫ/Ϫ mice) after Ang II infusion ( Figure 4A). Because 5-HT can cause contraction through RhoA/Rho-kinase signaling, 20,21 we repeated the 5-HT concentration-response experiment after a 30-minute incubation with the Rho-kinase inhibitor Y-27632 (1 mol/L) and found that it attenuated the response to 5-HT in Ang IIinfused mice (and Ang II-infused AT 1A Ϫ/Ϫ mice; Figure 4A). Y-27632 also significantly reduced 5-HT contraction in the vehicle-infused AT 1A ϩ/ϩ and AT 1A Ϫ/Ϫ mice, confirming the importance of Rho-kinase in 5-HT-induced contraction.…”
Section: Resultsmentioning
confidence: 99%
“…However, responses to 5-HT were markedly enhanced in the AT 1A ϩ/ϩ mice (but not the AT 1A Ϫ/Ϫ mice) after Ang II infusion ( Figure 4A). Because 5-HT can cause contraction through RhoA/Rho-kinase signaling, 20,21 we repeated the 5-HT concentration-response experiment after a 30-minute incubation with the Rho-kinase inhibitor Y-27632 (1 mol/L) and found that it attenuated the response to 5-HT in Ang IIinfused mice (and Ang II-infused AT 1A Ϫ/Ϫ mice; Figure 4A). Y-27632 also significantly reduced 5-HT contraction in the vehicle-infused AT 1A ϩ/ϩ and AT 1A Ϫ/Ϫ mice, confirming the importance of Rho-kinase in 5-HT-induced contraction.…”
Section: Resultsmentioning
confidence: 99%